THEORY OF CALCULATION OF EFFORT IN FORMING BIMETALLIC HARVESTING OF SEALING PIPE FITTING GAS TRANSPORTATION SYSTEM - , В. В., А. С. (Municipal economy of cities. Series: «Economy science», 2013)
We consider the residual stresses in the blanks for precision steam shut-off valves and calculation theory of effort in forming a bimetallic billets.